The European Survey on Adverse Systemic Reactions in Allergen Immunotherapy (EASSI): A paediatric assessment. Issue 1 (3rd November 2016) - Rodríguez del Río, Pablo; Vidal, Carmen; Just, Jocelyne; Tabar, Ana I.; Sanchez‐Machin, Inmaculada; Eberle, Peter; Borja, Jesus; Bubel, Petra; Pfaar, Oliver; Demoly, Pascal; Calderón, Moises A.
Abstract: Background: Safety data on 'real‐life' allergen immunotherapy (AIT) in children and adolescents is usually extrapolated from studies in adults. Methods: Patients aged 18 or under initiating aeroallergen AIT were evaluated in a prospective European survey. Patient profiles and systemic reactions (SRs) were recorded. Descriptive, univariate and multivariate analyses were used to identify risk factors for SRs. Results: A total of 1563 patients (mean ± SD age: 11.7 ± 3.9 years; rhinitis: 93.7%; asthma: 61.5%; polysensitization: 62.5%) and 1578 courses of AIT were assessed. Single‐allergen AIT was administered in 89.5% of cases (n = 1412; mites: 49%; grass pollen: 25.8%; tree pollen: 8.7%; Alternaria : 4.6%; dander: 0.8%; weed pollen: 0.6%). Subcutaneous AIT (SCIT) was used in 71.4% (n = 1127) of the treatments, including 574 (50.9%) with natural extracts. Sublingual AIT (SLIT) was used for the remaining 451 treatments (drops: 73.8%; tablets: 26.2%). The mean ± SD follow‐up period was 12.9 ± 3.3 months. The estimated total number of doses was 19, 669 for SCIT and 131, 550 for SLIT. Twenty‐four patients (1.53%) experienced 29 SRs. Respiratory (55.7%) and skin symptoms (37.9%) were most frequent. Anaphylaxis was diagnosed in 3 SRs (10.3%), and adrenaline was administered in 2 of these cases. In a univariate analysis, the risk of SRs was lower in mite‐sensitized patients and higher in cases of pollen polysensitization (>3), grass pollen extracts and the use of natural extracts (vs. allergoids). Conclusions: In a real‐life paediatric setting, AIT is safe. SRs are infrequent and generally not severe. Pollen polysensitization, grass pollen extracts and natural extracts (vs. allergoids) were risk factors for AIT‐associated SRs.